PENCEGAHAN PERNIKAHAN DINI DI KECAMATAN JOGOROTO KABUPATEN JOMBANG TAHUN 2022 MEMALUI PERAN KANTOR URUSAN AGAMA (KUA) - Nurhasim Muhammad Khafid; Muhammad Muhammad (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Marriage is interpreted as a contract or agreement that involves the intention to permit sexual relations using the terms 'nakaha' or 'zawaja'. Child marriage is a marriage with dispensation due to not meeting the legal requirements for marriage. Such marriage does not fulfill the criteria in terms of age sufficiency as stipulated in Article 7 of Law No. 16 of 2019 concerning the minimum age for marriage. In this case, it will investigate the incidence rate of early marriage at the Jogoroto Religious Affairs Office, the causes and consequences of early marriage, as well as the role of the Jogoroto Religious Affairs Office in preventing early marriage. This research is a field research. The data source for this study is the Office of Religious Affairs. The object of this study is the role of the KUA in efforts to reduce the incidence of early marriages. Data collection methods employed by the researcher include interviews, observations, and documentation. The analysis technique used in this research involves three steps: data reduction, data presentation, and conclusion drawing or verification.The results of this study can be summarized as follows: (1) Early marriages in the Jogoroto District have decreased from 2021 to 2022. (2)The causes of early marriages include economic factors, education, parents, biological factors, and pregnancies outside of marriage. (3) The KUA in the Jogoroto District, in its efforts to prevent early marriages, provides legal marriage counseling and collaborates with supportive parties and those directly involved with the target so that the desired outcomes can be easily achieved.